Development of children adopted to the United States following a social–emotional intervention in St. Petersburg (Russian Federation) institutions. Issue 3 (3rd July 2019) - Julian, Megan M.; McCall, Robert B.; Groark, Christina J.; Muhamedrahimov, Rifkat J.; Palmov, Oleg I.; Nikiforova, Natasha V.
ABSTRACT: This study is a post-adoption follow-up of social–emotional interventions in St. Petersburg, Russian Federation Baby Homes (BHs). Children previously resided in BHs and received Care as Usual (CAU, N  = 220), Training Only (TO, N  = 94), or Training plus Structural Changes (T + SC, N  = 45). This study examined intervention effects 0–6.5 years post-adoption to the United States, at age 9 months to 7 years old. Adoptive parents completed questionnaires on their child's social and behavioral development. Intervention graduates had better attachment security, less indiscriminate friendliness, and fewer behavior problems than CAU graduates. Children who had longer exposure to intervention conditions had better attachment security, but poorer executive function, externalizing and internalizing problems, and competence. Thus, although postinstitutionalized children were generally functioning in the normal range in early childhood and effect sizes were small, a social–emotional intervention in institutions is associated with modest benefits to attachment and behavior problems and apparent decrements to executive function.